Understanding the Role of Organizational Confidence on the Culture of Teacher Leadership in Public Schools in the Philippines - Santos, Ferdinand S. (Future Science / FSH-PH Publications, 2023)
The purpose of this study is to understand the role of organizational trust on the culture of teacher leadership in selected public-schools in the Philippines. The study utilized a qualitative research design involving public-school principals in Schools Division Marikina, Marikina City. Findings revealed that one of the leading themes that stood out in the responses was that teacher leadership is a skill that needs continuous development. The participants said that teacher leadership is being observed when school tasks are being properly managed and when there is a harmonious work environment in the institution. The most dominant challenges are the reluctance of teachers to accept challenging tasks, low self-confidence, and lack of compassion. Participants shared unique characteristics of leadership empowerment, such as being transparent, honest, responsible, and considerate. The majority of the participants agreed that organizational confidence can be achieved through teacher empowerment. Participants also stated that it is time for the organizational confidence to be established in order to effectively render a good quality education in the Philippines. Findings also revealed that being a good listener is a key factor in advocating teacher leadership and that building a working environment wherein everyone will have their own opportunity to experience leadership is also one the recommendations mentioned by the participants.